2009
DOI: 10.1002/cpp.605
|View full text |Cite
|
Sign up to set email alerts
|

Therapist characteristics influencing the quality of alliance in long‐term psychotherapy

Abstract: This study explored therapist characteristics associated with the development of working alliance in long-term therapies, up to 120 sessions. The quality of working alliance was rated by both patients (n = 201) and therapists (n = 61) at sessions 3, 12, 20 and every 20th successive session. Therapists' self-reported scores on the 'cold/detached' dimension of Inventory of Interpersonal Problems-64 tapping therapists' interpersonal style, such as being distanced, disconnected or indifferent, had a negative impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 37 publications
3
51
0
6
Order By: Relevance
“…However, the number of demographic variables and pre-treatment outcome measures used by Luborsky et al (1996) to evaluate the discriminant validity of the HAq-II-P was greater than those used in the present study. In addition, the Spanish-language HAq-II-T correlated significantly with therapist age, and though we are not aware of any existing research that has examined the relationship between the HAq-II-T and therapist age, Hersoug et al (2009) found that greater therapist age was significantly associated with greater therapist alliance scores on the WAI-T.…”
Section: Discussionmentioning
confidence: 77%
“…However, the number of demographic variables and pre-treatment outcome measures used by Luborsky et al (1996) to evaluate the discriminant validity of the HAq-II-P was greater than those used in the present study. In addition, the Spanish-language HAq-II-T correlated significantly with therapist age, and though we are not aware of any existing research that has examined the relationship between the HAq-II-T and therapist age, Hersoug et al (2009) found that greater therapist age was significantly associated with greater therapist alliance scores on the WAI-T.…”
Section: Discussionmentioning
confidence: 77%
“…Much of the variation in therapeutic alliance has been identified as provider-specific and not attributable to patient characteristics, (Baldwin et al, 2007) and clear provider techniques (e.g. being supportive and respectful, noting past successes, and attending to the patient's experience) are known to be correlated with strong alliances (Hersoug, Hoglend, Havik, von der Lippe, & Monsen, 2009). These approaches and skills may be amenable to change, suggesting that interventions directed at improving providers' abilities to create a partnership with patients that fosters patients' activation are possible.…”
Section: Discussionmentioning
confidence: 99%
“…In a later attachment study, however, Dinger et al (2009) revealed that therapists’ attachment security was not related to alliance development in general, but a higher “reoccupation” attachment style in therapists (i.e., being insecure of significant others’ feelings or tending to cling to and to control others) predicted worse therapist-patient alliances. Similarly, Hersoug et al (2009) found a worse patient- and therapist-rated alliance if the therapist was “cold” or “detached” in private life, whereas therapists’ representation of a more caring mother was associated with higher patient ratings of the therapeutic alliance. Schauenburg et al (2010), on the contrary, could not replicate these findings of therapists’ attachment styles in private life and patient-rated-alliance, but found that a higher attachment security of the therapist facilitated better alliance among severely impaired patients.…”
Section: Introductionmentioning
confidence: 90%